Holistic Parenting Method from al-Qur'an Perspective: Strengthening Family Resilience in Facing the Dynamics of Modern Life - Muammar Khadafi; Muhammad Ulul Azmi (Cigarskruie: Journal of Educational and Islamic Research, 2024)
Modern life is increasingly complex and dynamic, family resilience is a very crucial issue and the challenges are becoming more and more real. Family resilience refers to the ability of a family to survive, adapt, and thrive despite various pressures and challenges. The goal of this research is to create families that have the ability to adapt to these changes while still maintaining their values and integrity. The internalization of Islamic values in the family. For the type of research "Holistic Parenting Method", the author uses literature research. Literature research is research whose data collection technique is carried out by reading various literature related to information and its relevance to the research topic. Meanwhile, according to Lexy J. Moleong, literature research with field research uses a qualitative approach, namely research whose procedure produces descriptive data in the form of written or oral words from observed people and actors. The results of the Holistic parenting research with its five aspects provide a comprehensive approach in building family resilience. By setting a good example, creating positive habits, giving wise advice, being fair, and applying proportionate consequences, holistic parenting ensures that every aspect of family resilience legality and structure, physical, economic, socio-psychological, and socio-cultural is met.